2002
DOI: 10.1007/s10265-002-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

A brief note on the study of yieldin, a wall-bound protein that regulates the yield threshold of the cell wall

Abstract: Yielding of plant-cell walls is defined by the mechanical properties of walls such as their extensibility ( Phi for in vivo, phi for in vitro cell wall) and yield threshold ( Y for in vivo, y for in vitro cell wall). A protein named yieldin, isolated from the cell wall of growing hypocotyls of Vigna unguiculata L. (cowpea), has been demonstrated to regulate the pH dependency of y in the cell wall of the glycerinated hollow cylinder of the cowpea hypocotyl. This mini-review outlines the process of the discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A Ca 2+ chelator perfectly mimicked at pH 6 the acid-induced increase in wall extensibility (Ezaki et al, 2005). The reduction in the yield threshold in the pH 6–5 range was almost entirely due to a heat-sensitive component (possibly the protein “yieldin”; Okamoto-Nakazato, 2002). Instead, the acid-induced extensibility increase was comprised of a heat-sensitive (presumably expansin) and a heat-insensitive, Ca 2+ –pectate-dependent component.…”
Section: What About Diffusely Growing Cells In Land Plants?mentioning
confidence: 99%
“…A Ca 2+ chelator perfectly mimicked at pH 6 the acid-induced increase in wall extensibility (Ezaki et al, 2005). The reduction in the yield threshold in the pH 6–5 range was almost entirely due to a heat-sensitive component (possibly the protein “yieldin”; Okamoto-Nakazato, 2002). Instead, the acid-induced extensibility increase was comprised of a heat-sensitive (presumably expansin) and a heat-insensitive, Ca 2+ –pectate-dependent component.…”
Section: What About Diffusely Growing Cells In Land Plants?mentioning
confidence: 99%
“…During growth, the cell wall must selectively loosen the network to accommodate volumetric expansion of the cell and withstand the expansive forces generated by cell turgor pressure. The loosening of cell walls in plants is related to: expansin (McQueenMason and Cosgrove, 1995) being able to independently induce the acid-growth of the cell wall (Cleland, 1983); numerous enzymes and proteins in the cell walls being able to alter cell wall structure (Fry, 1995;Yuan et al, 2001;Okamoto-Nakazato, 2002;Van Sandt et al, 2007); and an increased cell wall susceptibility due to the action of expansin (Cosgrove, 1999).…”
mentioning
confidence: 99%
“…Expansin (Cosgrove 1997, Li et al 2003) and yieldin (Okamoto‐Nakazato 2002, Okamoto‐Nakazato et al 2000a, 2000b) have been reported as the wall‐loosening proteins, which mediate the acid growth of the plant cell wall. Expansin was isolated from growing tissue, such as cucumber hypocotyls (McQueen‐Mason et al 1992), tomato leaves (Keller and Cosgrove 1995), oat coleoptiles (Cosgrove and Li 1993, Li et al 1993) and deepwater rice (Cho and Kende 1997a, 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…Yieldin was isolated from cell wall of growing cowpea hypocotyls. Yieldin caused increase in the extensibility by decreasing the yielding threshold (Okamoto‐Nakazato 2002, Okamoto‐Nakazato et al 2000a, 2000b). Immunological analysis showed that the yieldin signal was highest in the apical pre‐elongation region and became weak gradually toward the mature region (Okamoto‐Nakazato et al 2001).…”
Section: Discussionmentioning
confidence: 99%